A Review of State Licensing Regulations to Determine Alignment with Best Practices to Prevent Human Norovirus Infections in Child-Care Centers. (May 2016) - Leone, Cortney M.; Jaykus, Lee-Ann; Cates, Sheryl M.; Fraser, Angela M.
Objectives: Close, frequent contact between children and care providers in child-care centers presents many opportunities to spread human noroviruses. We compared state licensing regulations for child-care centers with national guidelines written to prevent human noroviruses. Methods: We reviewed child-care licensing regulations for all 50 U.S. states and the District of Columbia in effect in June 2015 to determine if these regulations fully, partially, or did not address 14 prevention practices in four topic areas: ( 1 ) hand hygiene, ( 2 ) exclusion of ill people, ( 3 ) environmental sanitation, and ( 4 ) diapering. Results: Approximately two-thirds (8.9) of the 14 practices across all state regulations were partially or fully addressed, with few (2.6) fully addressed. Practices related to exclusion of ill people and diapering were fully addressed most often, while practices related to hand hygiene and environmental sanitation were fully addressed least often. Conclusion: Regulations based on guidelines for best practices are one way to prevent the spread of human noroviruses in child-care facilities, if the regulations are enforced. Our findings show that, in mid-2015, many state child-care regulations did not fully address these guidelines, suggesting the need to review these regulations to be sure they are based on best practices